Water Rites Reimagining Water in the West - Ellis, Jim (Calgary Institute for the Humanities, 2018)
What are the challenges surrounding water in Western Canada? What are our rights to water? Does water itself have rights? Water Rites: Reimagining Water in the West documents the many ways that water flows through our lives, connecting the humans, animals, and plants that all depend on this precious and endangered resource. Essays from scholars, activists, environmentalists, and human rights advocates illuminate the diverse issues surrounding water in Alberta, including the right to access clean drinking water, the competing demands of the resource development industry and Indigenous communities, and the dwindling supply of fresh water in the face of human-caused climate change. Statements from community organizations detail the challenges facing watersheds, and the actions being taken to mitigate these problems. With a special focus on Environmental and Indigenous issues, Water Rites explores how deeply water is tied to human life. These essays are complemented by full-colour portfolios of work by contemporary painters, photographers, and installation artists who explore our relation to water. Reproductions of historical paintings, engravings and film stills demonstrate how water has shaped our country's cultural imaginary from its beginnings, proving that water is a vital resource for our lives and our imaginations.